Training Together: How Another Human Trainee’s Presence Affects Behavior during Virtual Human-Based Team Training - Robb, Andrew; Kleinsmith, Andrea; Cordar, Andrew; White, Casey; Wendling, Adam; Lampotang, Samsun; Lok, Benjamin (Frontiers in ICT, 2016)
Despite research showing that team training can lead to strong improvements in team performance, logistical difficulties can prevent team training programs from being adopted on a large scale. A proposed solution to these difficulties is the use of virtual humans to replace missing teammates. Existing research evaluating the use of virtual humans for team training has been conducted in settings involving a single human trainee. However, in the real world multiple human trainees would most likely train together. In this paper, we explore how the presence of a second human trainee can alter behavior during a medical team training program. Ninety-two nurses and surgical technicians participated in a medical training exercise, where they worked with a virtual surgeon and virtual anesthesiologist to prepare a simulated patient for surgery. The agency of the nurse and the surgical technician were varied between three conditions: human nurses and surgical technicians working together; human nurses working with a virtual surgical technician; and human surgical technicians working with a virtual nurse. Variations in agency did not produce statistically significant differences in the training outcomes, but several notable differences were observed in other aspects of the team's behavior. Specifically, when working with a virtual nurse, human surgical technicians were more likely to assist with speaking up about patient safety issues that were outside of their normal responsibilities; human trainees spent less time searching for a missing item when working with a virtual partner, likely because the virtual partner was physically unable to move throughout the room and assist with the searching process; and more breaks in presence were observed when two human teammates were present. These results show that some behaviors may be influenced by the presence of multiple human trainees, though these behaviors may not impinge on core training goals. When developing virtual human-based training programs, designers should consider that the presence of other humans may reduce involvement during training moments perceived to be the responsibility of other trainees, and should consider that a virtual teammate's limitations may cause human teammates to limit their own behaviors in corresponding ways (e.g. searching less).